Expo Levante : Catologo Ufficiale. (Bari : Fiera Internazionale per il tempo libero, 1996)
Addamiano, Natale ; Amato, Nicola ; Basile, Giuseppina ; Battista, Fernando ; Bianchi, Giampaolo ; Bosco, Emilio ; Bracco, Anna Maria ; Burdi, Domenico ; Busco, Giuseppe ; Cacucciolo, Loredana ; Campa, Gabriella ; Campa, Paola ; Campanella, Vita Franca ; Capodacqua, Luigia ; Capossela, Giovanna ; Caprio, Mario ; Carli, Claudio ; Carma ; Cazzolla, Filippo Maria ; Chieppa, Manlio ; Circiello, Michele ; Consoli, Carmelo ; Cortese, Francesco ; Cramarossa, Oronzo ; Cusano, Vincenza ; D'Alessandro, Alberto ; Dall'Acqua, Francesco ; De Pasquale, Maria ; De Sario, Giuseppe ; Canosa, Giuseppe Di ; Priamo, Cesare Di ; D'Orazio, Patrizia ; Falotico, Lucia ; Fiermonte, Tommaso ; Fiorelli, Domenico ; Forte, Anna ; Gallo, Maresca Benito ; Gemmato, Pasquale ; Genchi, Gianpiero ; Giannakoulas, Giovanna Irdi ; Giordano, Bruno ; Giunta, Alessandro ; Grando, Lara ; Guagnano, Armando ; Iannelli, Rocco ; Iannetta, Orazio ; Lacatena, Giovanni ; Lapesara, Michele ; Laurelli, Antonio ; Leonardo, Sergio ; Lignano, Ferdinando ; Longo, Antonio ; Lorenzo, Corrado ; Lozupone, Enrico ; Maggiano, Elia ; Magrini, Giampiero ; Maiullari, Vito ; Marini, Renato ; Marotta, Angelo ; Mercuri, Rosario ; Miressi, Elvio ; Morea, Nicola ; Mosaico, Anna Nanette ; Moschella, Emilio ; Napoletano, Leonardo ; Negro, Benito A. ; Noia, Antonio ; Orfino, Francesca ; Palladino, Francesca ; Pancella, Vito ; Pantaleo, Pietro Giulio-Oasi ; Papino, Maria Pia ; Paradisi, Romolo ; Parisi, Alessandro ; Petronelli, Rossella ; Pisani, Angela ; Sasso, Cosima ; Sciolan, Renato ; Sebaste, Salvatore ; Tridente, Felice ; Triggiani, Rossella ; Tripoli, Angela ; Uva, Anna ; Vescovi, Giulia ; Violetta, Vito ; Viti, Vincenzo ; Zizzi, Angela ; Arcuri, Caterina ; Capasso, Peppe ; Cariati, Vanessa ; D'Avino, Daniela ; etc.
biografie
boek